Patients with recurrent syncope and implantable loop recorder exhibit better survival than the control group without implantable loop recorder. (25th November 2020) - Perings, C; Wolff, C; Wilk, A; Witthohn, A; Voss, R; Rybak, K
Abstract: Introduction: In 30% of patients with syncope, the underlying cause remains unexplained after clinical investigations. Unexplained syncope tends to recur, significantly impacting patients' quality of life of patients and mortality. Thus, there is a need for timely and more accurate diagnosis to initiate treatment. Dedicated care pathways are recommended by ESC guidelines. Purpose: Patients with recurrent syncope were followed over time and patient outcomes with ILR were compared to patients with the same syncope burden, age, gender and mortality risk score who did not receive an ILR. Method: A representative database of 4.9 million patients insured by German company statuary health insurances (BKK) was analysed over a time period of 10 years, 2007–17. Patients with recurrent syncope (two times ICD-10 GM diagnosis codes R55), age between 45–84 and no diagnosis code for the syncope were included in the analysis and followed for at least 2 years. Patients with ILR were matched to patients without ILR based on age, gender and Charlson Comorbidity index (CCI) using mahalanobis distances. The index event was the device implant in the ILR group and the second syncope event in the control group. Life expectancy, syncope hospitalisations, fall related injuries, health care costs, diagnoses and treatment rates were compared between the groups. Results: A total of 412 patients with ILR for recurrent unexplained syncope were matched to the control group. Overall mean age was 68, mean was CCI 2.7, 42% were females. The risk of death was 2.35 times higher in the control group during follow up as shown in Figure 1 (p-value logrank test <0.0001). Cardiovascular related diagnosis and treatment rates were higher in the ILR group with 69% of patients having a cardiology diagnosis compared to 41% in the control group. Over a quarter (27%) of ILR patients received an implantable cardiac device compared to 5% in the control group. Ablation rates were 7% in the ILR group compared to 0% in the control group. Median health care costs were € 3, 847 higher in the ILR group including the costs of the ILR implant, follow up and higher rates of cardiac treatments. These extra costs appear moderate given the substantially higher mortality risk in the control group. Conclusion: This study of patients with recurrent unexplained syncope shows a remarkable difference in life expectancy in patients with ILR compared to a matched control group. Two large claim data analysis have recently shown higher rates of cardiovascular death as well as all-cause mortality in patients with unexplained syncope. A more vigilant cardiac workup might be needed to identify a possible underlying cardiac condition. Higher rates of cardiac device therapy in the ILR group were likely to play an important role for their better life expectancy. Cardiac therapies such as pacemakers, defibrillators and ablation have also been shown to significantly improve patients' quality of life. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): The data analysis was funded by Medtronic